2016
DOI: 10.1111/cen.13031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on measures of arterial stiffness: a systematic review and meta‐analysis of randomized controlled trials

Abstract: SummaryBackground Low vitamin D has been associated with poor arterial compliance in observational studies. Arterial stiffness has prognostic value for cardiovascular disease risk. The aim of this systematic review was to clarify the literature surrounding the use of vitamin D to ameliorate arterial stiffness. Methods We conducted a systematic review of the MEDLINE, Scopus and EMBASE databases for randomized controlled clinical trials investigating the effect of vitamin D supplementation on pulse wave velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
57
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 53 publications
10
57
1
3
Order By: Relevance
“…At the same time, recent systematic reviews and meta-analyses concluded that VitD has no effect on markers of arterial stiffness (included RCTs: n = 7 [113]; n = 13 [114]) or markers of endothelial function (included RCTs: n = 16 [112]). In alignment with this narrative review, almost all of the published systematic reviews highlight the significant methodological heterogeneity in terms of dose and duration of treatment, which limits the interpretation of the findings and raises the need for a critical appraisal, over and beyond the reported results.…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, recent systematic reviews and meta-analyses concluded that VitD has no effect on markers of arterial stiffness (included RCTs: n = 7 [113]; n = 13 [114]) or markers of endothelial function (included RCTs: n = 16 [112]). In alignment with this narrative review, almost all of the published systematic reviews highlight the significant methodological heterogeneity in terms of dose and duration of treatment, which limits the interpretation of the findings and raises the need for a critical appraisal, over and beyond the reported results.…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%
“…Although some systematic reviews have used criteria to establish the quality of study design (i.e., allocation concealment, blinding, baseline comparability of groups, description of dropouts and intention-to-treat analysis), none of them have pooled the data according to the guidelines by Heaney [99]. Nevertheless, sensitivity analyses among the above analyses looking separately at either the effect of dose or duration of supplementation or baseline VitD status did not alter the null-effect findings [80,112,114]. …”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%
“…Мета-анализы указывают на отсутствие влияния приема витамина D на артериальное давление [50], ар-териальную жесткость [51,52] и эндотелиальную функ-цию [53]. На потенциальную пользу в отношении сердеч-но-сосудистой системы от приема высоких доз витамина D указывают данные ряда исследований; так, данные Zaleski и соавт.…”
Section: витамин D и сердечно-сосудистые заболеванияunclassified
“…This year alone, quantitative meta-analyses of arterial stiffness outcomes have been published by Upala et al [6] and Rodríguez et al [7] summarising 7 and 18 RCTs, respectively. A recent quantitative meta-analysis on peripheral blood pressure outcomes identified 46 independent vitamin D supplementation trials [5].…”
mentioning
confidence: 99%
“…These quantitative studies, although not included in the review by Veloudi et al [4], support the same conclusion which Veloudi et al [4] make from a qualitative review of RCTs, namely that vitamin D supplementation has no effect on arterial stiffness or blood pressure. However, Rodríguez et al [7] surmise that larger, well-designed RCTs are required to make sound conclusions on the effect of vitamin D supplementation on arterial stiffness. In terms of endothelial function, a quantitative meta-analysis published this year identified 16 RCTs [8], the summary of which also showed no effect of vitamin D supplementation.…”
mentioning
confidence: 99%